2012
DOI: 10.1177/1753425912444767
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of NLRP3 inflammasome in gingival fibroblasts by subgingival biofilms: Involvement of Porphyromonas gingivalis

Abstract: Recognition of pathogen-associated molecular patterns that activate IL-1 is regulated by inflammasomes, predominantly of the nucleotide-binding oligomerization domain-like receptor (NLR) family. NLRP3 inflammasome is involved in the innate immune responses in periodontal disease. This is an inflammatory condition that destroys the tooth-supporting (periodontal) tissues, initiated by the subgingival formation of multi-species biofilms, frequently including the Gram-negative species Porphyromonas gingivalis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
94
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 37 publications
4
94
1
Order By: Relevance
“…In contrast to our findings, it was recently reported that NLRP3 expression is downregulated by subgingival biofilm in primary gingival fibroblast tissue, partly due to P. gingivalis (33). The discrepancy between studies may be attributed to the different cell types studied or to the difference between a live single-type bacterial infection and a biofilm infection.…”
Section: Discussioncontrasting
confidence: 55%
“…In contrast to our findings, it was recently reported that NLRP3 expression is downregulated by subgingival biofilm in primary gingival fibroblast tissue, partly due to P. gingivalis (33). The discrepancy between studies may be attributed to the different cell types studied or to the difference between a live single-type bacterial infection and a biofilm infection.…”
Section: Discussioncontrasting
confidence: 55%
“…Additionally, our results rule out the possibility that P. gingivalis suppresses F. nucleatum-induced inflammasome activation through the reduction of endogenous levels of Nlrp3 or the other core components of its inflammasome. A recent study suggested that Nlrp3 is down-regulated by 33% in gingival fibroblast cultures colonized with a nine-species biofilm upon the inclusion of P. gingivalis (50). However, Il1b transcription was also reduced 35%, and it is therefore unclear whether reduced IL1b, rather than Nlrp3, may contribute to the reduced IL-1␤ secretion in that model.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of P. gingivalis to stimulate the first but not the second signal may be a rare trait of periodontopathogens [17]. In addition, it is known that subgingival biofilms down-regulate NLRP3 and IL-1β gene expression in gingival fibroblasts in vitro , with P. gingivalis being a critical component of the biofilms [41]. The present literature supports the notion that, as part of the polymicrobial community, P. gingivalis can disrupt host-microbial homeostasis by dampening the pathogen-sensing capacity of the host cells via inflammasomes [42].…”
Section: Discussionmentioning
confidence: 99%